2016
DOI: 10.3233/jad-150695
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study on Resting State Functional Connectivity in Behavioral Variant Frontotemporal Dementia and Alzheimer’s Disease

Abstract: Background/Objective: Alzheimer's disease (AD) and behavioral variant frontotemporal dementia (bvFTD) are the most common types of early-onset dementia. We applied longitudinal resting state functional magnetic resonance imaging (fMRI) to delineate functional brain connections relevant for disease progression and diagnostic accuracy. Methods: We used two-center resting state fMRI data of 20 AD patients (65.1 ± 8.0 years), 12 bvFTD patients (64.7 ± 5.4 years), and 22 control subjects (63.8 ± 5.0 years) at basel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
22
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 66 publications
7
22
0
2
Order By: Relevance
“…The human insular has an important role in attention, language, speech, working memory, and memory (Kelly et al., ). The increased functional connectivity between insula and SOFG was earlier reported in the Alzheimer's Disease(Balthazar et al., ; Hafkemeijer et al., ). Insula and SOFG play an important role in anterior frontoinsular‐cingulo‐orbitofrontal network often called the salience network which is related with the ability to direct attentional resources and goal‐relevant cognition (Menon, ).…”
Section: Discussionsupporting
confidence: 70%
“…The human insular has an important role in attention, language, speech, working memory, and memory (Kelly et al., ). The increased functional connectivity between insula and SOFG was earlier reported in the Alzheimer's Disease(Balthazar et al., ; Hafkemeijer et al., ). Insula and SOFG play an important role in anterior frontoinsular‐cingulo‐orbitofrontal network often called the salience network which is related with the ability to direct attentional resources and goal‐relevant cognition (Menon, ).…”
Section: Discussionsupporting
confidence: 70%
“…The precuneus was also described as particularly vulnerable for AD pathology, including cerebral atrophy and amyloid deposition [39]. The axons from the superior retina project via the parietal lobe portion of the optic radiation to the cuneal gyrus of the primary visual cortex, and some authors found decreased longitudinal functional connectivity between the precuneus and other cerebral area networks in AD [40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…First, while specific functional network connections were found to deviate between AD and bvFTD patients [12,27,28,60], we hypothesized that restricting our analysis to specific network regions may introduce bias and may unnecessary exclude other regions that show deficits at different stages of the disease [23,24,52,66]. The number of network regions that need to be distinguished to optimally differentiate between dementia-types still needs clarification.…”
Section: Discussionmentioning
confidence: 99%
“…Functional connectivity measures may inform on dementia state [23][24][25] or dementia progression [23][24][25] even well before clinical or structural differences can be detected [25,26]. Differences in functional connectivity strengths as measured with restingstate functional MRI (rs-fMRI) have been heralded as early and useful markers to differentiate AD and bvFTD patients [27,28].…”
Section: Introductionmentioning
confidence: 99%